2018
DOI: 10.1002/14651858.cd009376.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Supportive periodontal therapy (SPT) for maintaining the dentition in adults treated for periodontitis

Abstract: Supportive periodontal therapy (SPT) for maintaining the dentition in adults treated for periodontitis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 115 publications
2
128
0
4
Order By: Relevance
“…In a global view, establishing efficient protocols or adjuvant periodontal strategies to reduce the probability of reinfection and disease progression, with consequent improvement in dental maintenance, is still a challenge, independently of the population studied (Manresa et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In a global view, establishing efficient protocols or adjuvant periodontal strategies to reduce the probability of reinfection and disease progression, with consequent improvement in dental maintenance, is still a challenge, independently of the population studied (Manresa et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in general, the majority of evidence indicates that smokers are at increased risk for the presence of unresponsive periodontal pockets and further periodontal breakdown during PMT. In several studies, two‐ to seven‐fold higher risk for RP were reported in CS when compared with FS and NS …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized the benefits of periodontal maintenance therapy (PMT) in preserving the homeostasis of periodontal tissues obtained after active periodontal therapy (APT) performed through surgical and/or non‐surgical procedures . However, without establishing a regular program of clinical re‐evaluation, adequate biofilm control, and reinforcement of oral hygiene instructions, the benefits of PMT could not be maintained …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional mechanical plaque removal is a successful tool to maintain the results of SRP during the phase of supportive periodontal therapy for many years and decades for a long life with own natural teeth . ‒ Here the compliance of the patient is mandatory and one of the keys to successful supportive therapy .…”
Section: Introductionmentioning
confidence: 99%